Model Supplay Chain Management dan Perancangan Aplikasi E-SCM pada PT Indofood Sukses Makmur Tbk Bogasari Flour Mills Division - Ang, Hendry (Journal the Winners: Economics, Business, Management, and Information System Journal, 2014)
The purpose of this study is to analyze company business process by determining the appropriate model of supply chain at PT Indofood Sukses Makmur Bogasari and designing the e-SCM system that aims to facilitate the flow of information and products to the company, ranging from suppliers to customers. Research used Porter’s Five Forces analysis, value network analysis, order fulfillment based on the concept of decoupling point, EOQ (Economic Order Quantity) inventory model, and the method of designing an e-SCM system with Object Oriented Analysis Design (OOAD). The results of Porter’s Five Forces analysis show that bargaining power of suppliers and competition among similar companies had a strong tendency, while bargaining power of customers, new competitors, and product substitution had a weak tendency in the external environment. In addition, the value chain analysis results show the condition of the company's internal information flows were substandard, especially in the upstream of the business process in the company. Based on the concept of decoupling point, MTS was more appropriate to Bogasari in response to consumer demand. Furthermore, this study also proposed EOQ inventory model so that the company can manage inventory and order better as well as overcome some of the problems such as the uncertainty in the inventory levels of consumer demand and limited raw materials from suppliers. The e-SCM online system application designed with Object Oriented Analysis Design (OOAD) is expected to facilitate the flow of information and to integrate its customers and agents in supporting company business process, so the information between suppliers and customers becomes well integrated.